Changes in autonomic nervous function and influencing factors in a rat insular cortex electrical kindling model. (16th March 2020) - Ming, Qianwen; Ma, Hongtao; Li, Jia; Yang, Fan; Li, Jing; Liang, Jianmin; Li, Dan; Lin, Weihong
Highlights: We established a rat epilepsy model to imitate the development of unexpected death. We established this model by kindling the region of insular autonomic regulation. We conducted a long-time video surveillance to analyze the progress of death. We found the heart rate change and weight can influence the kindling time. Abstract: In mammals, the insular cortex plays an important role in autonomic regulation. In patients with insular epilepsy, seizures are always accompanied by autonomic changes. Accordingly, we aimed to establish an electrical kindling model in autonomic-mediating areas of the insular cortex, and to conduct a long-term observation of epileptic genesis in these animals until sudden unexpected death. To establish this model in adult rats, we implanted stimulation electrodes in the granular cell layer of the insular cortex, which controls the heart rate (HR) and respiratory rate (RR). Subsequently, seizure was induced successfully in 92.3 % of the rats, and typical autonomic changes were observed during these seizures. Interestingly, the model was established more easily in older rats, and the rats in which electrical stimulation led to a greater reduction in the HR. Moreover, death occurred in 25 % of the kindled rats. In conclusion, our kindling model demonstrates the ability of insular cortex stimulation to generate epilepsy. Our model thus offers a practical tool for studies of the role of the insular cortex in sudden unexpected death in epilepsy.